2016
DOI: 10.5812/traumamon.23573
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Corrective Exercise to Decrease Falling and Improve Functional Balance in Idiopathic Parkinson’s Disease

Abstract: Background:Posture instability and unsteady gait disorders in Parkinson’s Disease (PD) usually contribute to fall-related fractures. Fall-related trauma in PD is the most common reason for injury. Despite providing modern care for PD patients (PP) in the recent years, anti-PD drugs have no effect on falling. There is an urgent need to administer exercise interventions to reduce falls and related injuries in the rehabilitation program of PP.Objectives:To explore the effect of a selective 10-week corrective exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 51 publications
(50 reference statements)
0
19
1
Order By: Relevance
“…Postural instability is a cardinal feature of PD that improves with pharmacotherapy in milder disease stages but becomes less responsive as the disease progresses . Our patient cohort had high BBS scores consistent with an overall low risk of falling . Despite this, a prior history of 1 or more falls was common.…”
Section: Discussionmentioning
confidence: 76%
“…Postural instability is a cardinal feature of PD that improves with pharmacotherapy in milder disease stages but becomes less responsive as the disease progresses . Our patient cohort had high BBS scores consistent with an overall low risk of falling . Despite this, a prior history of 1 or more falls was common.…”
Section: Discussionmentioning
confidence: 76%
“…However, they require safety monitoring and are equipment-dependent. Research on alternative forms of exercise that could improve balance, gait, and function in patients with PD is scarce [12][13][14][15]. On balance, alternative physical therapies are worthy of consideration when selecting treatment options for people with this common chronic disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have established the beneficial effects of balance exercises on the prevention of idiopathic PD (31,61). In line with our findings, which showed that 8 weeks of ABCT caused no significant difference in FOF, FOG, and risk of fall in PD patients, the results of a study by Allen (2011) showed that low-intensity exercises had no effects on fall prevention (57).…”
Section: Discussionmentioning
confidence: 99%
“…Each session included 10 minutes of warm-up and stretching exercises, 40 minutes of postural realignment exercises, and 10 minutes of cooling down and stretching exercises (30). The postural realignment consisted of walking in different directions, static/dynamic marching, tandem walking (31), and ADLs. The standard guidelines regarding the frequency, volume, duration, intensity, and progression of exercises were applied (32,33).…”
Section: Interventional Planmentioning
confidence: 99%